Coping the arsenic toxicity in rice plant with magnesium addendum for alluvial soil of indo-gangetic Bengal, India - Paul, Sonali; Dey, Rupshali; Sarkar, Ipsita; Chakraborty, Ankit; Mondal, Sahil; Saha, Sreshtha; Mukherjee, Susmita (Journal of Environmental Engineering and Landscape Management, 2021)
Arsenic (As3+) is a toxic metalloid found in the earth’s crust, its elevated concentration is a concern for human health because rice is the staple grain in eastern part of India and the waterlogged rice field environment provides opportunity for more As3+ uptake. Magnesium (Mg2+) is an important plant nutrient. Present work is a search for reducing As3+ toxicity in plants through Mg2+ application. The findings are quite impressive, the root to shoot biomass ratio showed more than 1.5 times increase compared to the control. Total protein content increased 2 folds. Carbohydrate and chlorophyll content increased two to three times compared to control. On the other hand, Malondialdehyde content showed a decline with the application of increased Mg2+ dose. The in-silico study shows a better interaction with As3+ in presence of Mg2+ but interestingly without stress symptoms. These findings from the research indicate that Mg2+ application can be effective in reducing As3+ induced stress in plants.